COVID-19: a dental perspective - Gupta, Paridhi; A., Bhagyalakshmi; Mehta, Pranshu (International Journal Of Community Medicine And Public Health, 2020)
The novel coronavirus that has been posing threat and has caused a havoc all over the world. It has affected millions involving more than 200 countries and the death toll continuously increasing. Despite the efforts the outbreak is still on the rise owing to community spread. As of 9 April 2020, there have been 1,438,994 confirmed cases of COVID-19, including 85,586 deaths worldwide. COVID-19 although zoonotic in origin now is primarily transmitted form human-to-human. This article provides a brief overview of the etiology, pathophysiology, symptoms and management protocol in dentistry of this novel infection.